Health Education about Stunting in Tanjung Tiram Village and Wawatu Village, North Moramo District, South Konawe Regency - Majid, Ruslan; Sabilu, Yusuf; Jafriati, Jafriati; Yasnani, Yasnani; Lisnawaty, Lisnawaty; Nurmaladewi, Nurmaladewi (Abdi Masyarakat, 2023)
Stunting is a chronic nutritional problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. South Konawe Regency is one of the districts in Southeast Sulawesi which is also a contributor to stunting cases in Southeast Sulawesi. The prevalence of stunting in South Konawe Regency ranks 11th out of 17 districts/cities with a prevalence of 28%. The results of a preliminary survey in Tanjung Tiram Village and Wawatu Village, South Konawe Regency found that there are several maternal behaviors that cause stunting, namely some children under five do not get exclusive breastfeeding, do not understand about stunting and determine children's nutritional status so that they realize too late that their children are classified as stunting cases. The method of implementing activities is carried out offline. The intervention provided by providing education to mothers of toddlers and posyandu cadres using media modules, pamphlets and health counseling related to several topics namely the causes of stunting, the characteristics of stunting in children, the impact of stunting on children, stunting prevention measures including prevention since pregnancy, while breastfeeding, the benefits of breastfeeding provided exclusively, the benefits and planning of MP-ASI menus, nutritional status for cadres in stunting prevention and carried out Toddler weight check with Lalowaru Health Center officers, North Moramo District. The conclusion of this activity is that the local government is very good which is proven by full support during the activity process, as well as the participants / targets of the activity in this case pregnant women, toddler mothers, and posyandu cadres. Participants are very enthusiastic and active in activities when given material and also when given examples, participants gain new knowledge related to parenting in stunting prevention.